2002
DOI: 10.1172/jci0213588
|View full text |Cite
|
Sign up to set email alerts
|

Epimorphin expression in intestinal myofibroblasts induces epithelial morphogenesis

Abstract: The crypt-villus axis is the principal functional and anatomic unit of the small intestinal epithelium. Anchored stem cells in the crypts of Lieberkuhn give rise to proliferating daughter cells that differentiate into four major epithelial cell types, including the enterocyte, goblet cell, enteroendocrine cell, and Paneth cell. Following injuries to the intestine such as ischemia, irradiation, trauma, and small bowel resection, or during recovery from inflammatory diseases such as Crohn disease, rapid renewal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
31
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 45 publications
3
31
0
Order By: Relevance
“…However, it is known that Bmp2 and 4 are highly expressed in the condensed mesenchyme underlying sites of future villus formation and may inhibit crypt formation in the overlying epithelium (Karlsson et al, 2000). Recent evidence that Bmp signaling mediates part of the function of epimorphin in forming the crypt-villus axis further supports a morphogenetic role for Bmps in the small intestine (Fritsch et al, 2002). One feature of the abnormal phenotype generated by transgenic expression of noggin is hyperplasia of the epithelium and the presence of numerous ectopic crypts.…”
Section: Discussionmentioning
confidence: 93%
“…However, it is known that Bmp2 and 4 are highly expressed in the condensed mesenchyme underlying sites of future villus formation and may inhibit crypt formation in the overlying epithelium (Karlsson et al, 2000). Recent evidence that Bmp signaling mediates part of the function of epimorphin in forming the crypt-villus axis further supports a morphogenetic role for Bmps in the small intestine (Fritsch et al, 2002). One feature of the abnormal phenotype generated by transgenic expression of noggin is hyperplasia of the epithelium and the presence of numerous ectopic crypts.…”
Section: Discussionmentioning
confidence: 93%
“…Deletion analyses of epimorphin have revealed that the morphogenic and vesicle-fusion functions are separable: the the C-terminal SNARE and TM domains are essential for syntaxin-mediated vesicular fusion (Chen and Scheller, 2001;Giraudo et al, 2006) but they are dispensable for epimorphinmediated morphogenic activity . Despite these differences and the many studies in a diverse range of tissues in which extracellularly presented epimorphin has been shown to regulate developmental processes (Bascom et al, 2005;Fritsch et al, 2002;Hirai et al, 1998;Hirai et al, 2001;Hirai et al, 1992;Lehnert et al, 2001;Oka and Hirai, 1996;Oka et al, 2006;Qin et al, 2005;Radisky et al, 2003;Takebe et al, 2003;Tulachan et al, 2006;Yoshino et al, 2006), the Epimorphin (also known as syntaxin 2) acts as an epithelial morphogen when secreted by stromal cells of the mammary gland, lung, liver, colon, pancreas and other tissues, but the same molecule functions within the cell to mediate membrane fusion. How this molecule, which lacks a signal sequence and contains a transmembrane domain at the Cterminus, translocates across the plasma membrane and is secreted to become a morphogen, and how it initiates morphogenic events is not clear.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that epimorphin has morphogenetic effects on multiple epithelial tissues, including those of skin, hair follicle, lung, intestine, mammary gland, pancreas, gall bladder and liver. [4][5][6][7][8][9][10] In addition, several investigators have reported changes in the distribution of epimorphin-positive cells in inflammatory diseases of the lung and liver. [11][12][13][14] Epimorphin not only regulates morphogenesis but also functions as a mesenchymal regulator of epithelial repair.…”
mentioning
confidence: 99%
“…[11][12][13][14] Epimorphin not only regulates morphogenesis but also functions as a mesenchymal regulator of epithelial repair. 10,12,14,15 The importance of epithelial-mesenchymal transition in the development of renal fibrosis has been extensively analyzed and characterized. 2,[16][17][18][19][20][21][22] However, there have been no reports of studies analyzing the involvement of epimorphin, which is the key molecule for epithelial-mesenchymal interaction, in renal fibrosis.…”
mentioning
confidence: 99%